Prevalence and concordance of HER2-low and HER2-ultralow status between historical and rescored results in a multicentre study of breast cancer patients in China - Hong Lv; Junqiu Yue; Qingfu Zhang; Fangping Xu; Peng Gao; Haifeng Yang; Xiu Nie; Lingfei Kong; Guanjun Zhang; Jianming Li; Shiwei Xiao; Hongmei Wu; et al. (Breast Cancer Research)
Abstract Background Accurately assessing HER2-low (immunohistochemistry [IHC] 1 + and IHC 2+/in situ hybridization [ISH]–) and HER2-ultralow (IHC > 0 < 1+) is essential given the emergence of novel therapies. Thorough understanding of the reproducibility of rescoring IHC stained slides or re-staining archived tissue slides is essential. Methods 2,869 breast cancer patients diagnosed between July 2021 and July 2022 from 10 hospitals in China were included in this multicentre study. The prevalence of different HER2 expression levels and distribution of HER2 IHC scores were assessed by HER2 status determination from rescored historical slides. Concordance was evaluated across historical results versus rescored results, historical results versus re-stained results, and leading center results versus local site results. Clinicopathological characteristics were retrospectively analyzed as well. Results HER2 IHC 0, IHC 1+, IHC 2+, and IHC 3 + were identified in 682 (23.8%), 871 (30.4%), 801 (27.9%), and 515 (18.0%) cases, respectively. HER2-positive, HER2-low, and HER2 IHC 0 (HER2-ultralow and IHC null) were identified in 21.7%, 54.5%, and 23.8% of cases, respectively. The prevalence of HER2-ultralow and IHC null was 10.6% and 13.2%, respectively. The concordance for HER2-ultralow was 43.3%; 30% of cases that were scored as HER2-ultralow at local sites were rescored as HER2-null and 26.7% of cases were rescored as IHC 1 + at the leading site. Overall, there was substantial agreement (83.1%) between rescored and historical IHC results. A high concordance rate of 91.7% was observed for HER2-low classification. Conclusions This is the first multicenter study to determine the prevalence of HER2-low and HER2-ultralow based on rescored results in the Chinese breast cancer population. The concordance analysis carries important implications for the diagnosis of HER2-low and HER2-ultralow cases in clinical practice. The relatively low concordance in identifying HER2-ultralow suggested that the reproducibility of scoring HER2-ultralow needed to be improved through training. Trial registration ClinicalTrials.gov identifier NCT05203458.